Short Communication: Viability and environmental effect to conidial germination of antagonistic fungi that potential as biological control of Colletotrichum gloeosporoides caused antracnose disease on chili - NURBAILIS NURBAILIS; MARTINIUS MARTINIUS; VERRY AZNIZA (Biodiversitas Journal of Biological Diversity, 2018)
Authors. 2018. Short Communication: Viability and environmental effect to conidial germination of antagonistic fungi that potential as biological control of Colletotrichum gloeosporoides caused antracnose disease on chili. Biodiversitas 19: 974-977. Some of antagonistic fungi from chili rhizosphere were potential to suppress the growth of colletotrichum gloeosporoides in vitro. This present study was aimed to observe the viability of antagonistic fungi and effect of temperature and ultraviolet light to its conidial germination. We targeted to obtain the isolate with the best viability and high resistance to temperature and ultraviolet changes. The experiment used a completely randomized design consisted of nine treatments and four replication. The treatment were nine of antagonistic fungi isolates from chili rhizosphere that consisted of two genera, Trichoderma and Paecilomyces, each comprised four isolates and unidentified isolate (X isolate). These four isolates were considered as replication for observation. The observed parameters observe included the width of colony, density of conidia, germination of conidia, effect of temperature and ultraviolet light changes to conidial germination. The results showed that antagonistic fungi from the genus Trichoderma had the best viability (the width of colony = 39.68-56.92 cm2, density of conidia 40.50-57.50 x 109 conidia/mL and germination of conidia > 80%) and highest resistance to temperature and ultraviolet changes compared with the other fungi used in this study.